Dietary L-citrulline modulates the growth performance, amino acid profile, and the growth hormone/insulin-like growth factor axis in broilers exposed to high temperature - Uyanga, Victoria Anthony; Zhao, Jingpeng; Wang, Xiaojuan; Jiao, Hongchao; Onagbesan, Okanlawon M.; Lin, Hai (Frontiers in Physiology, 2022)
Heat stress adversely affects the growth performance, muscle development, and protein metabolism in poultry. L-Citrulline (L-Cit), is a non-essential amino acid that is known to stimulate muscle protein synthesis under stress conditions. This study investigated whether L-Cit could influence the growth performance, amino acid, and protein metabolism broilers exposed to high ambient temperature. In a 2 x 2 factorial arrangement, Arbor acre broilers (288 chickens) were fed with basal diet (CON) or 1% L-Cit supplemented diet and later subjected to either thermoneutral (TNZ: 24°C, 24h/d) or heat stress (HS: 35°C for 8h/d) environment for 21 d. The results showed that L-Cit diet promoted the body weight and body weight gain of broilers higher than the CON diet, and it further alleviated HS suppression of body weight and feed intake at certain periods (P < 0.05). Plasma urea, uric acid, glucose, and total cholesterol were elevated during HS, whereas, the triglyceride content was decreased (P < 0.05). Serum amino acids including citrulline, alanine, aspartate, and taurine were decreased by HS. L-Cit supplementation restored the citrulline level and alleviated HS induction of 3-methylhistidine (P < 0.05). L-Cit supplementation increased the plasma growth hormone (GH) and insulin-like growth factor-1 (IGF-1) concentration, as well as the GH concentration in the breast muscle (P < 0.05). The mRNA expression showed that HS elicited tissue-specific responses by upregulating several growth factors in the breast muscle, but downregulated the GH receptor, GH binding protein, and IGF-1 expression in the hypothalamus. L-Cit supplementation upregulated the GHRH and IGFBP2 expression in the hypothalamus. L-Cit also upregulated the expression of IGF-1R and IGFBP2 in the breast muscle of HS broilers. The total mTOR protein level in the breast muscle of HS broilers was also increased by L-Cit diet (P < 0.05). Therefore, this study demonstrated that HS negatively affected the growth performance of broilers and dysregulated the expression of growth factors related to protein metabolism. Contrarily, L-Cit promoted the growth responses of broilers via its stimulation of circulating GH/IGF-1 concentration. To certain extents, L-Cit supplementation elicited protective effects on the growth performance of HS broilers by diminishing protein catabolism.